Neurotrophic keratitis: current challenges and future prospects - Versura, Piera (Eye Brain, 2018)
Neurotrophic keratitis (NK) is a degenerative corneal disease caused by damage of trigeminal corneal innervation, which leads to spontaneous epithelial breakdown and corneal ulceration. The impairment of corneal sensory innervation causes the reduction of both protective reflexes and trophic neuromodulators that are essential for the vitality, metabolism, and wound healing of ocular surface tissues. A wide range of ocular and systemic conditions, including herpetic keratitis, ocular chemical burns, corneal surgery, diabetes, multiple sclerosis, and neurosurgical procedures, can cause NK by damaging trigeminal innervation. Diagnosis of NK requires careful investigation of any ocular and systemic condition associated with the disease, complete ocular surface examination, and quantitative measurement of corneal sensitivity. The clinical stages of NK range from corneal epithelial alterations (stage 1) to persistent epithelial defect (stage 2) and ulcer (stage 3), which may progress to corneal perforation. Management of NK is based on clinical severity, and the aim of the therapy is to halt the progression of corneal damage and promote epithelial healing. Although several medical and surgical treatments have been proposed, no therapies are currently available to restore corneal sensitivity, and thus, NK remains difficult and challenging to treat. The purpose of this review is to summarize available evidence on the pathogenesis, diagnosis, and treatment of NK. Novel medical and surgical therapies including the topical administration of nerve growth factor and corneal neurotization are also described.